Skeletal muscle mass and body fat in relation to successful ageing of older adults: The multi-national MEDIS study. (September 2016) - Tyrovolas, Stefanos; Haro, Josep-Maria; Mariolis, Anargiros; Piscopo, Suzanne; Valacchi, Giuseppe; Bountziouka, Vassiliki; Anastasiou, Foteini; Zeimbekis, Akis; Tyrovola, Dimitra; Foscolou, Alexandra; Gotsis, Efthimios; Metallinos, George; et al.
Highlights: Successful agers had better body composition rates compared with the rest sample. Increase in skeletal muscle index was positively associated with successful ageing. Increase in body fat% was inversely associated with successful ageing. Abstract: Background: The determinants that promote successful ageing still remain unknown. The aim of the present work was to evaluate the role of skeletal muscle mass and body fat percentage (BF%), in the level of successful ageing. Methods: during 2005–2011, 2663 older (aged 65–100 years) from 21 Mediterranean islands and the rural Mani region (Peloponnesus) of Greece were voluntarily enrolled in the study. Appendicular skeletal muscle mass (ASM), skeletal muscle mass index (SMI) and BF% were calculated using population formulas. Dietary habits, energy intake, expenditure and energy balance were derived throughout standard procedures. A successful ageing index ranging from 0 to 10 was used. Results: The mean ASM mass was 24 ± 6.0 kg, the SMI was 0.84 ± 0.21 and the BF% was 44%. Females had lower SMI and higher BF% in comparison with males, respectively [(SMI: 0.66 ± 0.09 vs. 1.03 ± 0.11; BF%: 51% vs. 34%, (p < 0.001)]. High successful agers had better rates in ASM (p = 0.01), SMI (p < 0.001) and BF% (p < 0.001), compared with the medium and low successful ones. Changes in SMI [b-coefficient (95% CI):2.14 (1.57 to 2.71)] were positively associated with successful ageing, while changes in BF% [b-coefficient (95% CI): −0.04 (−0.05 to −0.03)] were inversely associated with successful ageing. Results from sensitivity analysis showed that the effects of variations on body composition were consistent, less pronounced in the positive energy balance group and more pronounced among the oldest old. Conclusions: Body composition changes seem to be associated with lower quality of life in the older adults, as measured through successful ageing.